Does computerized tomography change the treatment decision in pediatric medial epicondyle fractures? - (:unkn) unknown (ARSMB-KVBMG, 2019)
The amount of displacement in medial epicondylar fracture is one of the most important criteria for treatment decision. The displacement of medial epicondyle fractures of the humerus may be underestimated by standard AP and lateral views of elbow. The aim of the current study is to show the clinical relavance of computerized tomography (CT) for medial epicondyle fractures. A retrospective analysis on patients with medial epicondyle fracture was performed. Measurements were performed by 9 reviewer, there were 12 cases available for review with both radiographs and CT. The difference between measurement of AP Xray versus frontal and axial CT scans was found to be statistically significant for 1st and 2nd assessments (p=0.001). The decision for operative treatment was higher after evaluation with CT for both first and second assessment and this was statistically significant (p=0,0001). CT is found to be superior to determine the real amount of the fracture displacement and was relavant for treatment decision of pediatric medial epicondylar fractures. We also found a better interobserver agreement for axial CT scans relative to treatment decision. Level of evidence : IV. © 2019, Acta Orthopaedica Belgica.
Keywords: Computerized tomography; Pediatric medial epicondyle fractures; Treatment decision